(untitled) (Research, Society and Development, 2022)
Early diagnosis of Autism Spectrum Disorder (ASD) is associated with significant gains in children’s cognitive and adaptive functioning. For this, the use of screening tools for early signs of the disorder such as the Modifield Checklist for Autism in Toddlers (M-CHAT) is indicated. Thus, the objective of this study was to verify the use of M-CHAT for the early detection of suspected cases of ASD by physicians at the Family Health Units (USF) in Anápolis - GO. The work is a primary, observational, prevalence, cross-sectional, descriptive and quantitative study. The research was carried out at the following USF in Anápolis – GO: USF Recanto do Sol, USF Filostro Machado, USF Bairro de Lourdes, USF Bandeiras, USF Annex Itamaraty, ESF Vila União and USF Parque Iracema. The sample was for convenience (n=24), and data collection at the USF was performed by applying a questionnaire that verifies the use of the M-CHAT instrument among physicians. Among the participants, 33.3% knew the M-CHAT instrument and 50% of them used it, and this use was made after the initial consultation if they suspected ASD characteristics in the patient (75%) or during the initial consultation (25% ). This study was in agreement with the current literature, where the majority of physicians participating in the research do not recognize having knowledge and skills for the diagnosis of ASD and are unaware of a specific protocol to aid in screening.